Bionic layered composite material as well as preparation method and application thereof

By introducing para-aldehyde benzoic acid modified polyvinyl alcohol, melamine borate and two-dimensional nanosheets into the bionic layered material, a highly ordered layered structure is solved, and it is difficult for existing materials to have both high strength and high strength. The problem of toughness achieves high strength and high toughness of the material and expands its application range.

CN119431982APending Publication Date: 2025-02-14BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411380972.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing bionic layered materials are difficult to have both high strength and high toughness, which limits their application range.

Method used

By introducing para-aldehyde benzoic acid modified polyvinyl alcohol, melamine borate and two-dimensional nanosheets, a highly ordered bionic layered structure is formed, which enhances the interface adhesion between the layered structure and the polymer matrix, and Improve the overall strength and toughness of the material through multiple supramolecular interactions.

Benefits of technology

It is achieved to improve the overall strength and toughness of the layered material while maintaining the lighter quality of the material, and the prepared layered block density is low, and the three-point bending strength and specific strength are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431982A_ABST
    Figure CN119431982A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite materials, and particularly relates to a bionic layered composite material and a preparation method and application thereof. The bionic layered composite material provided by the invention is prepared from p-formylbenzoic acid modified polyvinyl alcohol, melamine borate and a two-dimensional nanosheet, the p-formylbenzoic acid modified polyvinyl alcohol is obtained by carrying out aldolization reaction on polyvinyl alcohol and p-formylbenzoic acid, and the molar ratio of the polyvinyl alcohol to the p-formylbenzoic acid is 1: (0.05-0.40); the mass ratio of the melamine borate to the p-formylbenzoic acid modified polyvinyl alcohol is 1: (2-10); the mass percentage content of the two-dimensional nanosheets in the bionic layered composite material is 5-60%. The composite material provided by the invention has good mechanical strength and toughness, and also has good flame retardant property and electromagnetic shielding property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a bionic layered composite material and a preparation method and application thereof. Background Art

[0002] During the long evolution process, biological structures such as shells have formed highly complex and fine layered structures that can provide extremely high strength at a relatively light weight; their main components are inorganic calcium carbonate and a small amount of organic matrix, which form lightweight and high-strength layered materials through interlacing and arrangement. Based on the in-depth understanding of the structure and mechanical enhancement mechanism of natural shells, bionic artificial layered materials have emerged, and the preparation of bionic layered composites based on two-dimensional materials such as MXene and graphene has become a research hotspot. These materials achieve excellent mechanical properties and functional characteristics by imitating the layered structure of natural shells. However, most of the existing bionic layered materials cannot have both strength and toughness, which limits their scope of application. Therefore, it is crucial to develop a bionic layered composite material that can have both high strength and high toughness. Summary of the invention

[0003] In view of this, the present invention provides a bionic layered composite material and a preparation method and application thereof. The bionic layered composite material provided by the present invention has good mechanical strength and toughness, and expands its application range.

[0004] In order to solve the above technical problems, the present invention provides a bionic layered composite material, including p-formylbenzoic acid-modified polyvinyl alcohol, melamine borate and two-dimensional nanosheets;

[0005] The p-formylbenzoic acid-modified polyvinyl alcohol is obtained by acetalization reaction of polyvinyl alcohol and p-formylbenzoic acid, wherein the molar ratio of the polyvinyl alcohol to the p-formylbenzoic acid is 1:0.05-0.40;

[0006] The mass ratio of the melamine borate to the p-formylbenzoic acid modified polyvinyl alcohol is 1:2-10;

[0007] The mass percentage of the two-dimensional nanosheets in the bionic layered composite material is 5-60%.

[0008] Preferably, the two-dimensional nanosheets include MXene nanosheets, MoS2 two-dimensional nanosheets, WS2 two-dimensional nanosheets or MoTe2 two-dimensional nanosheets.

[0009] Preferably, the preparation method of melamine borate comprises the following steps:

[0010] Dissolving melamine and boric acid in water and then leaving the water to stand to obtain the melamine borate;

[0011] The molar ratio of melamine to boric acid is 1:1.8-2.2.

[0012] Preferably, the dissolution temperature is 85-95°C and the dissolution time is 25-35 min;

[0013] The standing temperature is 15 to 30° C. and the standing time is 12 to 24 hours.

[0014] Preferably, the preparation method of the modified polyvinyl alcohol comprises the following steps:

[0015] The modified polyvinyl alcohol is obtained by mixing a p-formylbenzoic acid solution, a polyvinyl alcohol solution and a hydrochloric acid solution for acetalization reaction and then mixing with methanol for precipitation.

[0016] Preferably, the solvent of the p-formylbenzoic acid solution includes dimethyl sulfoxide or N,N-dimethylacetamide; the p-formylbenzoic acid solution, the polyvinyl alcohol solution and the hydrochloric acid solution are mixed to obtain a molar ratio of polyvinyl alcohol to p-formylbenzoic acid of 1:0.05-0.40;

[0017] The solvent of the polyvinyl alcohol solution includes dimethyl sulfoxide or N,N-dimethylacetamide; the mass concentration of the polyvinyl alcohol solution is 5-10%;

[0018] The molar concentration of the hydrochloric acid solution is 0.8 to 1.2 mol / L;

[0019] The mass ratio of the polyvinyl alcohol solution to the hydrochloric acid solution is 38-42:1;

[0020] The temperature of the acetalization reaction is 70-80° C. and the time is 12-24 hours.

[0021] The present invention also provides a method for preparing the bionic layered composite material described in the above technical solution, comprising the following steps:

[0022] The p-formylbenzoic acid-modified polyvinyl alcohol, melamine borate, two-dimensional nanosheets and an organic solvent are mixed to obtain a mixed solution;

[0023] The mixed solution is molded to obtain the bionic layered composite material.

[0024] Preferably, the organic solvent comprises dimethyl sulfoxide or N,N-dimethylformamide;

[0025] The mass ratio of the melamine borate to the p-formylbenzoic acid modified polyvinyl alcohol is 1:2-10; the mass ratio of the total mass of the melamine borate and the p-formylbenzoic acid modified polyvinyl alcohol to the mass ratio of the two-dimensional nanosheets is 100:5-60.

[0026] Preferably, the forming method includes coating to form a film or laminating the film materials coated to form a film and then hot pressing to prepare a block.

[0027] The present invention also provides the application of the bionic layered composite material described in the above technical solution or the bionic layered composite material prepared by the preparation method described in the above technical solution in spacecraft, automobiles and buildings.

[0028] The present invention provides a bionic layered composite material, comprising p-formylbenzoic acid-modified polyvinyl alcohol, melamine borate and two-dimensional nanosheets; the p-formylbenzoic acid-modified polyvinyl alcohol is obtained by acetalization reaction of polyvinyl alcohol and p-formylbenzoic acid, and the molar ratio of polyvinyl alcohol to p-formylbenzoic acid is 1:0.05-0.40; the mass ratio of melamine borate to p-formylbenzoic acid-modified polyvinyl alcohol is 1:2-10; the mass percentage of two-dimensional nanosheets in the bionic layered composite material is 5-60%. The present invention introduces two-dimensional nanosheets into the composite material to form a highly ordered bionic layered structure, and the present invention enhances the interfacial adhesion between the layered structure and the polymer matrix through multiple supramolecular interactions between the layered structure and the interlayer material. When subjected to external forces, the layered composite material provided by the present invention provides an energy dissipation pathway under multiple interactions, can effectively transmit stress, and improves the overall strength and toughness of the layered material while maintaining a relatively light weight of the material. The density of the prepared layered block is as low as 1.23g / cm 3 The three-point bending strength can reach 179.47±1.98Mpa, and the specific strength is as high as 146.0MPa·m 0.5 / Mg -3 .

[0029] The components of the biomimetic layered composite material in the present invention have hydrogen bonds, π-π interactions, and hydrophobic-hydrophobic multiple supramolecular interactions, which bring good environmental stability to the material. The interlayer substances are effectively adsorbed on the surface of the two-dimensional nanosheets through supramolecular interactions, forming a "sandwich" structure coupled by supramolecular effects, so that the two-dimensional nanosheets are cross-linked, so that the prepared biomimetic layered material can resist the erosion of various chemical solvents.

[0030] The conductive nanosheets in the present invention have a unique two-dimensional sheet microstructure, which enables them to exhibit extremely high efficiency in electromagnetic shielding applications. At the same time, the highly ordered layered structure constructed by the present invention enables the material to have multiple shielding capabilities, allowing the layered composite material to exhibit excellent electromagnetic interference shielding performance.

[0031] The melamine borate in the layered structure of the present invention can be used as a boron-nitrogen synergistic flame retardant. When the material is exposed to a high-temperature flame, an isolation layer is formed in the layered structure, which effectively prevents heat from being transferred to the inside and isolates oxygen, thereby improving the flame retardant properties of the bionic layered composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM image of the bionic layered block B1 prepared in Example 8;

[0033] Figure 2 The line graphs of the WAXS orientation factors of the film materials F1 to F7 prepared in Examples 1 to 7 corresponding to different nanosheet contents;

[0034] Figure 3 The actual pictures of F6 prepared in Example 6 at different burning times;

[0035] Figure 4 The actual pictures of F8 prepared in Comparative Example 3 at different burning times;

[0036] Figure 5 The electromagnetic shielding performance test results of the bionic layered composite material F4 to F7 films prepared in Examples 4 to 7 are shown in FIG.

[0037] Figure 6 The three-point bending test curves of the bionic layered block B1 prepared in Example 8 and the sample B4 of Comparative Example 4;

[0038] Figure 7 A bar chart comparing the three-point bending strength and modulus of the bionic layered block B1 prepared in Example 8 and the block samples B2 and B3 prepared in Comparative Examples 1 and 2;

[0039] Figure 8 is the stress-strain curve of the layered composite film F1 prepared in Example 1;

[0040] Fig. 9 The following are actual comparison diagrams of the layered composite film F1 prepared in Example 1 before and after being immersed in water, acetone, ethanol, toluene, methanol and dichloromethane solvents for 7 days. DETAILED DESCRIPTION

[0041] The invention provides a bionic layered composite material, comprising p-formylbenzoic acid-modified polyvinyl alcohol, melamine borate and two-dimensional nanosheets.

[0042] In the present invention, the p-formylbenzoic acid-modified polyvinyl alcohol is obtained by acetalization reaction of polyvinyl alcohol and p-formylbenzoic acid, and the molar ratio of the polyvinyl alcohol to p-formylbenzoic acid is 1:0.05-0.40, and can be 1:0.1-0.3.

[0043] As an embodiment of the present invention, the preparation method of the modified polyvinyl alcohol comprises the following steps:

[0044] The modified polyvinyl alcohol is obtained by mixing a p-formylbenzoic acid solution, a polyvinyl alcohol solution and a hydrochloric acid solution for acetalization reaction and then mixing with methanol for precipitation.

[0045] As an embodiment of the present invention, the solvent of the p-formylbenzoic acid solution may include dimethyl sulfoxide or N,N-dimethylacetamide, which may be dimethyl sulfoxide; the mass concentration of the p-formylbenzoic acid solution may be 5-10%.

[0046] As an embodiment of the present invention, the solvent of the polyvinyl alcohol solution includes dimethyl sulfoxide or N,N-dimethylacetamide, which may be dimethyl sulfoxide; the mass concentration of the polyvinyl alcohol solution may be 5-10%, specifically 5%, 8% or 10%.

[0047] As an embodiment of the present invention, the molar concentration of the hydrochloric acid solution can be 0.8-1.2 mol / L, and can be specifically 1.0 mol / L. As an embodiment of the present invention, the mass ratio of the polyvinyl alcohol solution to the hydrochloric acid solution can be 38-42:1, and can also be 40:1. In the present invention, the hydrochloric acid acts as a catalyst, and protonation in the aldol acetal reaction enhances the electrophilicity of the carbonyl group, making the nucleophilic addition reaction process easier to proceed.

[0048] As an embodiment of the present invention, the molar ratio of polyvinyl alcohol to p-formylbenzoic acid in the system obtained by mixing the p-formylbenzoic acid solution, the polyvinyl alcohol solution and the hydrochloric acid solution can be 1:0.05-0.40, or 1:0.1-0.3;

[0049] As an embodiment of the present invention, the mixing comprises the following steps:

[0050] Ultrasonic dispersion of p-formylbenzoic acid in a solvent to obtain a p-formylbenzoic acid solution;

[0051] The p-formylbenzoic acid solution is added dropwise to the polyvinyl alcohol solution, and then the hydrochloric acid solution is added.

[0052] As an embodiment of the present invention, the temperature of the acetalization reaction can be 70-80°C, specifically 70°C, 75°C or 80°C; the time of the acetalization reaction can be 12-24h, specifically 12h, 15h, 17h, 20h, 22h or 24h.

[0053] The present invention has no special requirement on the amount of methanol used, and the precipitation can be carried out in a conventional manner in the art.

[0054] As an embodiment of the present invention, the preparation method of melamine borate comprises the following steps:

[0055] Melamine and boric acid are dissolved in water and then allowed to stand to obtain the melamine borate.

[0056] As a specific embodiment of the present invention, the molar ratio of melamine to boric acid can be 1:1.8-2.2, specifically 1:2. As an embodiment of the present invention, the water can be deionized water; the dissolution temperature can be 85-95°C, specifically 85°C, 90°C or 95°C; the dissolution time can be 25-35min, specifically 25min, 30min or 35min. As an embodiment of the present invention, the dissolution can be accompanied by stirring.

[0057] As an embodiment of the present invention, the standing temperature can be 15-30°C, specifically 15°C, 20°C, 25°C or 30°C; the standing time can be 12-24h, or 18-20h. The present invention forms a salt by standing the melamine and boric acid. Due to the effect of hydrogen bonding, melamine and boric acid can be arranged together in an orderly manner to form a relatively stable hydrogen bond complex.

[0058] As an embodiment of the present invention, the standing still may further include: filtering the system after the standing still, washing and drying the solid obtained by the filtration in sequence to obtain the melamine borate. The present invention has no special requirements for the filtration and can adopt the conventional methods in the art. As a specific embodiment of the present invention, the water used for washing can be deionized water, and the temperature of the water used for washing can be 0 to 10°C, or 3 to 5°C; the number of times of washing can be 2 times, 3 times or 4 times. As a specific embodiment of the present invention, the drying can be freeze-drying.

[0059] As an embodiment of the present invention, the two-dimensional nanosheet may include a MXene nanosheet, a MoS2 two-dimensional nanosheet, a WS2 two-dimensional nanosheet or a MoTe2 two-dimensional nanosheet, and may be specifically a MXene nanosheet; the MXene nanosheet may be a Ti3C2T x Nanosheets, Ti3C2F x Nanosheets, Ti3CNF x Nanosheets or Mo2CF x Nanosheets. The present invention has no special requirements for the preparation method of the two-dimensional nanosheets, and conventional methods in the art can be used.

[0060] As an embodiment of the present invention, the mass ratio of melamine borate and p-formylbenzoic acid modified polyvinyl alcohol in the bionic layered composite material is 1:2-10, and can be specifically 1:2, 1:3, 1:4, 1:5, 1:6, 1:7 or 1:8; the mass percentage of two-dimensional nanosheets in the bionic layered composite material is 5-60%, and can be specifically 5.6%, 10.6%, 19.2%, 30.3%, 40.9% or 52.1%.

[0061] As an embodiment of the present invention, the thickness of the bionic layered composite material may be 0.1 μm to 10 cm.

[0062] The present invention also provides a method for preparing the bionic layered composite material described in the above technical solution, comprising the following steps:

[0063] The p-formylbenzoic acid-modified polyvinyl alcohol, melamine borate, two-dimensional nanosheets and an organic solvent are mixed to obtain a mixed solution;

[0064] The mixed solution is molded to obtain the bionic layered composite material.

[0065] The present invention mixes p-formylbenzoic acid-modified polyvinyl alcohol, melamine borate, two-dimensional nanosheets and an organic solvent to obtain a mixed solution. As an embodiment of the present invention, the organic solvent may include dimethyl sulfoxide (DMSO) or N,N-dimethylformamide (DMF), and may be specifically dimethyl sulfoxide.

[0066] As an embodiment of the present invention, the mass ratio of the melamine borate and the p-formylbenzoic acid modified polyvinyl alcohol can be 1:2-10, specifically 1:2, 1:3, 1:4, 1:5, 1:6, 1:7 or 1:8; the mass ratio of the total mass of the melamine borate and the p-formylbenzoic acid modified polyvinyl alcohol to the two-dimensional nanosheets can be 100:5-60.

[0067] As a specific embodiment of the present invention, the mixing may include the following steps:

[0068] dissolving p-formylbenzoic acid-modified polyvinyl alcohol in a portion of an organic solvent to obtain a p-toluic acid-modified polyvinyl alcohol solution;

[0069] dispersing the two-dimensional nanosheets in the remaining organic solvent to obtain a two-dimensional nanosheet dispersion;

[0070] Melamine borate and the two-dimensional nanosheet dispersion are sequentially added into the p-toluic acid-modified polyvinyl alcohol solution to obtain a mixed solution.

[0071] The present invention has no special limitation on the volume percentage of the partial organic solvent to the total organic solvent, as long as it can be completely dissolved. In the present invention, non-covalent bonding such as hydrogen bonding and π-π interaction will occur between the mixed p-formylbenzoic acid-modified polyvinyl alcohol, melamine borate and two-dimensional nanosheets.

[0072] After obtaining the mixed solution, the present invention shapes the mixed solution to obtain the bionic layered composite material. As a specific embodiment of the present invention, the shaping method may include coating to form a film or laminating the film material coated to form a film and then hot pressing to prepare a block. As an embodiment of the present invention, the coating method may be scraping, specifically, scraping the mixed solution on the substrate surface to form a film, peeling the film from the substrate surface and drying to obtain a film-like bionic layered composite material. The scraping process in the preparation process of the present invention will apply shear force to the mixed solution, prompting the two-dimensional nanosheets to achieve orderly arrangement parallel to the substrate direction in the fluid along the coating direction, thereby forming a highly ordered bionic layered structure. As an embodiment of the present invention, the substrate may be a glass plate, a polypropylene (PP) plate, a polyvinyl chloride (PVC) plate, a polycarbonate (PC) plate, an aluminum plate or a stainless steel plate.

[0073] As an embodiment of the present invention, after obtaining the film-like bionic layered composite material, the coated film material can be stacked and then hot-pressed to prepare a block. As an embodiment of the present invention, the film material can be cut into films of uniform size before stacking; pre-forming can be performed before hot pressing, and the pre-forming pressure can be 1-5MPa, the pre-forming temperature can be 30-50°C, and the pre-forming pressure and heat preservation time can be 1-6h. As an embodiment of the present invention, the hot pressing pressure can be 10-50MPa, and can also be 20-40MPa; the hot pressing temperature can be 50-150°C, and can also be 100-130°C; the hot pressing pressure and heat preservation time can be 6-24h, and can also be 10-18h.

[0074] The present invention also provides the application of the bionic layered composite material described in the above technical scheme or the bionic layered composite material prepared by the preparation method described in the above technical scheme in spacecraft, automobiles and buildings; specifically, it can be used as lightweight and high-strength structural parts in spacecraft, high-strength and tough structural parts in automobiles, and fireproof materials for buildings.

[0075] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0076] Example 1

[0077] (1) Preparation of PVA-CBA

[0078] Dissolving polyvinyl alcohol in dimethyl sulfoxide at 90° C. to obtain a polyvinyl alcohol solution with a mass concentration of 10%;

[0079] Ultrasonic dispersion of p-formylbenzoic acid in dimethyl sulfoxide for 10 minutes to obtain a p-formylbenzoic acid solution with a mass concentration of 5%;

[0080] 50 mL of p-formylbenzoic acid solution was added dropwise into 200 mL of polyvinyl alcohol solution, and then 5 mL of hydrochloric acid solution with a molar concentration of 1 mol / L was added. The mixed solution (the molar ratio of polyvinyl alcohol and p-formylbenzoic acid in the mixed solution was 1:0.30) was subjected to acetal reaction at 75°C (with stirring) for 24 hours, and then precipitated in methanol to obtain p-formylbenzoic acid-modified polyvinyl alcohol PVA-CBA.

[0081] (2) Preparation of melamine borate

[0082] Melamine and boric acid were dissolved in 50 mL of deionized water at a molar ratio of 1:2 (90°C, with stirring), the resulting solution was naturally cooled to 25°C and allowed to stand for 24 hours, filtered, and the filtered solid was washed three times with deionized water at 0°C and freeze-dried to obtain white crystalline melamine borate.

[0083] (3) Ti3C2T x Preparation of nanosheets

[0084] 0.8 g of LiF was added to 10 mL of 9 mol / L hydrochloric acid solution, and the mixture was stirred continuously. 0.5 g of Ti3AlC2 powder was slowly added. After etching at 40 °C for 24 h, the system was washed with deionized water several times until the solution was neutral. The supernatant was discarded, and the precipitate was dispersed with the solution and centrifuged for 1 h to separate the single layer or few layers of Ti3C2T x Nanosheets with unetched MAX phase to obtain Ti3C2T x Nanosheets.

[0085] (4) Preparation of biomimetic layered composite materials

[0086] Dissolve 1.0 g of PVA-CBA in dimethyl sulfoxide to obtain a PVA-CBA solution with a mass concentration of 10%;

[0087] 0.071g Ti3C2T x The nanosheets were dispersed in dimethyl sulfoxide to obtain Ti3C2T with a mass concentration of 5%. x Nanosheet dispersion;

[0088] 0.2 g melamine borate and Ti3C2T3 were added to the PVA-CBA solution. x nanosheet dispersion to obtain a mixed solution;

[0089] The mixed liquid was scraped on the surface of the plasma-treated glass plate substrate using a scraper and then allowed to stand at 70°C for 24 hours to form a film. After the film was formed, it was peeled off from the surface of the glass substrate and vacuum dried at 70°C to obtain a film-like bionic layered composite material with a thickness of 5 μm, which was recorded as F1 film.

[0090] Example 2

[0091] The bionic layered composite material was prepared according to the method of Example 1, except that Ti3C2T x The mass of the nanosheets was adjusted from 0.071 g to 0.143 g, and the prepared bionic layered composite material was recorded as F2 film.

[0092] Example 3

[0093] The bionic layered composite material was prepared according to the method of Example 1, except that Ti3C2T x The mass of the nanosheets was adjusted from 0.071 g to 0.285 g, and the prepared bionic layered composite material was recorded as F3 film.

[0094] Example 4

[0095] The bionic layered composite material was prepared according to the method of Example 1, except that Ti3C2T x The mass of the nanosheets was adjusted from 0.071 g to 0.522 g, and the prepared bionic layered composite material was recorded as F4 film.

[0096] Example 5

[0097] The bionic layered composite material was prepared according to the method of Example 1, except that Ti3C2T x The mass of the nanosheets was adjusted from 0.071 g to 0.832 g, and the prepared bionic layered composite material was recorded as F5 film.

[0098] Example 6

[0099] The bionic layered composite material was prepared according to the method of Example 1, except that Ti3C2T x The mass of the nanosheets was adjusted from 0.071 g to 1.30 g, and the prepared bionic layered composite material was recorded as F6 film.

[0100] Example 7

[0101] The bionic layered composite material was prepared according to the method of Example 1, except that Ti3C2T xThe mass of the nanosheets was adjusted from 0.071 g to 1.80 g, and the prepared bionic layered composite material was recorded as F7 film.

[0102] Example 8

[0103] Prepare F1 film according to the method of Example 1;

[0104] The F1 film was cut into films of uniform size and stacked into multilayer films. After being moistened with the film-making solution, the films were preheated and pressed for 3 h at a pressure of 3 MPa and a temperature of 40°C to obtain a prefabricated block. The prefabricated block was hot pressed for 10 h at a pressure of 30 MPa and a temperature of 130°C to obtain a block bionic layered composite material, recorded as B1.

[0105] Comparative Example 1

[0106] A film-like biomimetic layered composite material was prepared according to the method of Example 2, except that no two-dimensional nanosheets were added to the mixed solution;

[0107] The prepared membrane-like bionic layered composite material is cut into films of uniform size and stacked into multi-layer films. After being moistened with a membrane-making solution, the films are preheated and pressed for 3 h at a pressure of 3 MPa and a temperature of 40°C to obtain a prefabricated block. The prefabricated block is hot pressed for 10 h at a pressure of 30 MPa and a temperature of 130°C to obtain a block composite material, which is recorded as B2.

[0108] Comparative Example 2

[0109] A film-like biomimetic layered composite material was prepared according to the method of Example 2, except that melamine borate was not added to the mixed solution;

[0110] The prepared membrane-like bionic layered composite material is cut into films of uniform size and stacked into multi-layer films. After being moistened with a membrane-making solution, the films are preheated and pressed for 3 h at a pressure of 3 MPa and a temperature of 40°C to obtain a prefabricated block. The prefabricated block is hot pressed for 10 h at a pressure of 30 MPa and a temperature of 130°C to obtain a block composite material, which is recorded as B3.

[0111] Comparative Example 3

[0112] Prepare PVA-CBA according to the method of Example 1;

[0113] Dissolving PVA-CBA in dimethyl sulfoxide to obtain a PVA-CBA solution with a mass concentration of 10%;

[0114] The PVA-CBA solution was coated on the surface of the plasma-treated glass plate substrate using a doctor blade and then allowed to stand at 70°C for 24 hours to form a film. The film was then peeled off from the glass substrate surface and dried in a vacuum at 70°C to obtain a film material with a thickness of 5 μm, which was recorded as F8 film.

[0115] The thickness and content of each component of the materials prepared in Examples 1 to 8 and Comparative Examples 1 to 3 are listed in Table 1.

[0116] Comparative Example 4

[0117] The natural pearl oyster was cut into a size of 10*10 mm and polished to a thickness of 5 mm to obtain a natural shell block, which was recorded as B4.

[0118] Table 1 Thickness and physical composition of the composite materials prepared in Examples 1 to 8 and Comparative Examples 1 to 3

[0119]

[0120] The material B1 prepared in Example 8 was examined by scanning electron microscopy to obtain a SEM image, as shown in FIG. Figure 1 As shown by Figure 1 It can be seen that the bionic layered composite material prepared by the present invention has a layered structure with a highly ordered arrangement, which is similar to natural mother-of-pearl.

[0121] The biomimetic layered composite films F1 to F7 prepared in Examples 1 to 7 were subjected to WAXS testing. Figure 2 The line graph of its orientation factor corresponding to different nanosheet contents is given by Figure 2 The data can verify that the nanosheets in the layered structure of F1~F7 have a highly ordered arrangement microstructure.

[0122] The flame retardant properties of the film materials F6 and F8 prepared in Example 6 and Comparative Example 3 were tested. Figure 3 These are the actual pictures of F6 burning at different times. Figure 4 This is a real picture of F8 burning at different times. Figure 3 and Figure 4 It can be seen that F6 can extinguish the flame in a short time compared with F8, showing good flame retardant performance. However, the flame retardant performance of comparative example 3 is weaker, the combustion lasts for a long time, and it is not easy to extinguish itself.

[0123] The electromagnetic shielding performance of the bionic layered composite materials F4-F7 films prepared in Examples 4-7 was tested in a test frequency range of 8.2-12.4 GHz. The results are as follows: Figure 5 As shown. Figure 5It can be seen that the trend of the curve in the figure is relatively flat, indicating that within the frequency range of the band shown in the figure, the shielding effectiveness of different samples (F4 to F7) has not changed significantly, verifying that it has good electromagnetic shielding effectiveness within the X-band range.

[0124] The block samples of Example 8 (B1) and Comparative Examples 1 (B2), 2 (B3), and 4 (B4) were subjected to a three-point bending test, and the results of the three-point bending strength and modulus are listed in Table 2. The three-point bending test curves of the B1 and B4 samples are shown in Table 2. Figure 6 shown.

[0125] Table 2 Three-point bending strength and modulus of block samples prepared in Example 8 and Comparative Examples 1, 2, and 4

[0126]

[0127] According to Table 2, a columnar comparison chart of three-point bending strength and modulus is drawn, such as Figure 7 Combining Table 2 and Figures 6-7 It is proved that the block bionic layered composite material provided by the present invention has better mechanical strength and toughness than natural shells.

[0128] The F1 film prepared in Example 1 was subjected to a tensile test to obtain a stress-strain curve, as shown in FIG. Figure 8 As shown. Figure 8 The analysis shows that the tensile strength of F1 film is 467.5MPa and the toughness is 40.3MJ / m 3 ,Depend on Figure 8 It can be proved that the bionic layered composite film provided by the present invention has excellent mechanical strength and toughness.

[0129] The layered composite film F1 prepared in Example 1 was immersed in water (H2O), acetone (Acetone), ethanol (EtOH), toluene (Toluene), methanol (MeOH) and dichloromethane (DCM) solvents for stability testing. Fig. 9 This is a comparison of the actual objects before and after soaking for 7 days. Fig. 9 It can be seen that the bionic layered composite material prepared in Example 1 has good resistance to chemical solvents and can remain stable for a long time in a variety of solvents.

[0130] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A bionic layered composite material, characterized in that: These include p-formylbenzoic acid-modified polyvinyl alcohol, melamine borate, and two-dimensional nanosheets; The p-formylbenzoic acid-modified polyvinyl alcohol is obtained by acetalization reaction of polyvinyl alcohol and p-formylbenzoic acid, wherein the molar ratio of the polyvinyl alcohol to the p-formylbenzoic acid is 1:0.05-0.40; The mass ratio of the melamine borate to the p-formylbenzoic acid modified polyvinyl alcohol is 1:2-10; The mass percentage of the two-dimensional nanosheets in the bionic layered composite material is 5-60%.

2. The bionic layered composite material according to claim 1, characterized in that: The two-dimensional nanosheets include MXene nanosheets, MoS2 two-dimensional nanosheets, WS2 two-dimensional nanosheets or MoTe2 two-dimensional nanosheets.

3. The bionic layered composite material according to claim 1, characterized in that: The preparation method of the melamine borate comprises the following steps: Dissolving melamine and boric acid in water and then leaving the water to stand to obtain the melamine borate; The molar ratio of melamine to boric acid is 1:1.8-2.

2.

4. The bionic layered composite material according to claim 3, characterized in that: The dissolution temperature is 85-95°C and the dissolution time is 25-35 minutes; The standing temperature is 15 to 30° C. and the standing time is 12 to 24 hours.

5. The bionic layered composite material according to claim 1, characterized in that: The preparation method of the modified polyvinyl alcohol comprises the following steps: The modified polyvinyl alcohol is obtained by mixing a p-formylbenzoic acid solution, a polyvinyl alcohol solution and a hydrochloric acid solution for acetalization reaction and then mixing with methanol for precipitation.

6. The bionic layered composite material according to claim 5, characterized in that: The solvent of the p-formylbenzoic acid solution includes dimethyl sulfoxide or N,N-dimethylacetamide; the p-formylbenzoic acid solution, the polyvinyl alcohol solution and the hydrochloric acid solution are mixed to obtain a system in which the molar ratio of polyvinyl alcohol to p-formylbenzoic acid is 1:0.05-0.40; The solvent of the polyvinyl alcohol solution includes dimethyl sulfoxide or N,N-dimethylacetamide; the mass concentration of the polyvinyl alcohol solution is 5-10%; The molar concentration of the hydrochloric acid solution is 0.8 to 1.2 mol / L; The mass ratio of the polyvinyl alcohol solution to the hydrochloric acid solution is 38-42:1; The temperature of the acetalization reaction is 70-80° C. and the time is 12-24 hours.

7. The method for preparing the biomimetic layered composite material according to any one of claims 1 to 6, comprising the following steps: The p-formylbenzoic acid-modified polyvinyl alcohol, melamine borate, two-dimensional nanosheets and an organic solvent are mixed to obtain a mixed solution; The mixed solution is molded to obtain the bionic layered composite material.

8. The preparation method according to claim 7, characterized in that: The organic solvent includes dimethyl sulfoxide or N,N-dimethylformamide; The mass ratio of the melamine borate to the p-formylbenzoic acid modified polyvinyl alcohol is 1:2-10; the mass ratio of the total mass of the melamine borate and the p-formylbenzoic acid modified polyvinyl alcohol to the mass ratio of the two-dimensional nanosheets is 100:5-60.

9. The preparation method according to claim 7, characterized in that: The forming method includes coating to form a film or laminating the film materials coated to form a film and then hot pressing to prepare a block.

10. Use of the bionic layered composite material according to any one of claims 1 to 6 or the bionic layered composite material prepared by the preparation method according to any one of claims 7 to 9 in spacecraft, automobiles and buildings.